2023
DOI: 10.1002/ejoc.202301002
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional coatings hinging on the catechol/amine interplay

Maria Laura Alfieri,
Lucia Panzella,
Alessandra Napolitano

Abstract: Design and implementation of functional coatings is a topic of active research in a variety of health‐related applications, most of which require wet adhesion. The powerful wet adhesion of mussel byssus proteins rich in DOPA and lysine residues provided a clue to realize that the combination of a catechol and an amine component has a specific role in the interfacial adhesion. From this natural model, polydopamine (PDA)‐based coatings have been developed that result from the oxidative polymerization of dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 158 publications
0
2
0
Order By: Relevance
“…Inspired by the composition of adhesive proteins in mussels, Lee and co-workers 16,17 have shown that dopamine (DA) through the self-polymerization process can form thin, surface-adherent polydopamine films (PDA) 18,19 onto a wide range of inorganic and organic materials, including noble metals, oxides, polymers, semiconductors, and ceramics. 20–26…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the composition of adhesive proteins in mussels, Lee and co-workers 16,17 have shown that dopamine (DA) through the self-polymerization process can form thin, surface-adherent polydopamine films (PDA) 18,19 onto a wide range of inorganic and organic materials, including noble metals, oxides, polymers, semiconductors, and ceramics. 20–26…”
Section: Introductionmentioning
confidence: 99%
“…15 Inspired by the composition of adhesive proteins in mussels, Lee and co-workers 16,17 have shown that dopamine (DA) through the self-polymerization process can form thin, surface-adherent polydopamine films (PDA) 18,19 onto a wide range of inorganic and organic materials, including noble metals, oxides, polymers, semiconductors, and ceramics. [20][21][22][23][24][25][26] On the other hand, carbon-based nanomaterials are one of the most widely discussed, researched and applied synthetic nanomaterials, due to their diverse capabilities, such as excellent electronic, magnetic and optical properties. At the same time, their chemical versatility allows them to be easily manipulated in laboratory and industrial environments, to be biocompatible and to be considered as a chemically robust platform.…”
Section: Introductionmentioning
confidence: 99%